Relationship Marketing and Customer Satisfaction: A Conceptual Perspective - Deborah O. Aka; Oladele J. Kehinde; Olaleke O. Ogunnaike (Bina Nusantara University, 2016)
This article examined the existing body of literature on transaction and relationship marketing. The specific objectives were to develop a conceptual framework to establish the relationship between relationship marketing and customer satisfaction and to examine the components of relationship marketing on the present ever dynamic world of business. The study identified relationship marketing variables and their impact on customer satisfaction. The framework aimed to provide insights into the studies on relationship marketing factors such as trust, commitment, communication, and service quality influence on customer satisfaction. The model provided a basis for empirical studies on the factors of relationship marketing and outcomes of customer satisfaction in developing nations. The study recommends that relationship marketing dimensions such as building customer’s trust, commitment to customers, communication, and service quality should be properly managed and maintained by service providers in Nigeria. This helps in building customer satisfaction and in the long-run customer loyalty.